Influence of Hydroxyl Groups of Quaternized Chitosan Derivatives on Antioxidant Activity - Wang, Gang; Li, Qing; Dong, Fang; Guo, Zhanyong (Asian Journal of Chemistry, 2014)
Four quaternized chitosan derivatives i.e., N-phenmethyl-N,N-dimethyl chitosan, N-(2-hydroxyl-phenmethyl)-N,N-dimethyl chitosan, N-(4-hydroxyl-phenmethyl)-N,N-dimethyl chitosan and N-(3,4-dihydroxyl-phenmethyl)-N,N-dimethyl chitosan were synthesized and their antioxidant activity against hydroxyl radicals was assessed. The result indicated that all the quaternized chitosan derivatives have better hydroxyl radical scavenging activity than chitosan and the antioxidant activity of derivatives increases when more hydroxyl groups are grafted.